Assessment and Quantification of Foam Cells and Lipid Droplet–Accumulating Microglia in Mouse Brain Tissue Using BODIPY Staining - Boaz Maiyo; Sanna Loppi; Helena Morrison; Kristian Doyle (Bio-Protocol)
This paper presents a refined, user-friendly protocol for using boron-dipyrromethene (BODIPY) to assess and quantify foam cells and lipid droplet–accumulating microglia (LDAM) in mouse brain tissue. The protocol aims to enhance existing methodologies by offering precise and efficient evaluation of foam cells and LDAM burden in various neuropathological conditions linked to lipid metabolism and neuroinflammation. A notable challenge in analyzing tissue from mouse models of these neurodegenerative disorders is the interference caused by the autofluorescent molecule lipofuscin. Our protocol addresses this issue with specific steps that effectively distinguish BODIPY fluorescence from lipofuscin autofluorescence, using advanced imaging techniques and filter settings to ensure accurate and reliable analysis. By providing a straightforward and accessible method, this research aims to facilitate the broader adoption of BODIPY-based techniques for detailed foam cell and LDAM analysis in mouse brain tissue, potentially enhancing diagnostic capabilities and deepening our understanding of how these cells contribute to neurodegenerative disease mechanisms.